An investigation of hindsight bias in nascent venture activity - Cassar, Gavin; Craig, Justin (Journal of Business Venturing, 2009)
We posit that individuals who are actively engaged in activities to develop their own venture will exhibit hindsight bias when recalling their startup experiences. We observe that those who fail to develop their startup activity into an operating business demonstrate substantial hindsight bias concerning the probability of venture formation. In particular, the recalled probability of success, reported after their decision to quit, is lower than the probability of success solicited during the nascent process. We argue that the systematic distortion of the past has important implications for individuals involved in the venturing process. Specifically, we suggest that these individuals are at risk of overestimating their chances of success when starting future nascent activity if they do not correct for their optimistic tendencies. The evidence from this study suggests it is important to recognize that what nascent entrepreneurs believe they experienced, and what they actually experienced, may not be equivalent.